Pendampingan Program Branding Desa Pagelaran Sebagai Destinasi Eduwisata Gerabah Malang Selatan - Juariyah, Lohana; Syihabudhin, Syihabudhin (Jurnal Pengabdian Masyarakat Akademisi, 2024)
Community based tourism is a concept of active participation with the purpose of increasing the prosperity of the local people as well as keeping the environmental quality, preserving the cultural heritage, and socio-cultural values. There are plenty of government effort to optimizing the potential of tourism using this concept. Tourism village, for instance, is one of the focus of Indonesian Government initiated in order to reduce poverty. Desa Pagelaran has a huge potential as this village producing a handcrafted terracotta pots that the knowledge has passed on generation to generation. The arising problem in this place was lack of innovation, generation gaps hinder the knowledge and skill transfer, and only a few families left are producing the terracotta pots. This community development program aims to rebranding the village as a Tourism Village. The program then divided into three sequence starting from planning, execution, and evaluation stage. The outcome of this program is video profile, social media as a promotion tools, and the arrangement of POKDARWIS (Kelompok Sadar Wisata) which then aiming to strengthen the brand of Desa Pagelaran as a Tourism Village.